2015
DOI: 10.1016/j.toxlet.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of human Nrf2 antibodies: A tale of two proteins

Abstract: The Nrf2 transcription factor is a master regulator of the cellular defense against oxidative and electrophilic stress. An increase in Nrf2 protein levels and an accumulation of Nrf2 in the nucleus are key parts of the Nrf2 activation mechanism. The western blot technique remains the most widely used method to assess these changes. A well-characterized, specific antibody that is commercially available would greatly enhance these studies in the field. Here, an apparently highly specific Nrf2 monoclonal antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 26 publications
0
29
0
3
Order By: Relevance
“…Our data suggested that Ginseng pretreatment was correlated with remarkable induction of Nrf2 downstream target markers, including NQO1, HO1, SOD2 and Gpx in the cortex, indicating the importance of Nrf2 activation in Ginseng’s neuroprotection. Since currently there is no effective commercial Nrf2 antibody (Lau et al, 2013 ; Kemmerer et al, 2015 ), it limits the direct measurement of Nrf2 protection. Together, our findings showed that Ginseng pretreatment protected against the progression and the extent of acute ischemic damage, attenuated acute ischemic sensorimotor deficit, and promoted long-term functional recovery, which might through Nrf2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggested that Ginseng pretreatment was correlated with remarkable induction of Nrf2 downstream target markers, including NQO1, HO1, SOD2 and Gpx in the cortex, indicating the importance of Nrf2 activation in Ginseng’s neuroprotection. Since currently there is no effective commercial Nrf2 antibody (Lau et al, 2013 ; Kemmerer et al, 2015 ), it limits the direct measurement of Nrf2 protection. Together, our findings showed that Ginseng pretreatment protected against the progression and the extent of acute ischemic damage, attenuated acute ischemic sensorimotor deficit, and promoted long-term functional recovery, which might through Nrf2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Western blots were performed as previously described [31] with some modifications. Cytoplasmic and nuclear extracts were prepared using the Nuclear Extraction Kit (Cayman Chemical Company, Ann Arbor, MI, USA), and the protein concentration was determined using the Pierce™ BCA Protein Assay Kit (Thermo Fisher, Waltham, MA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…It is worth noting that some of the earlier studies targeted a non-specific band for Nrf2 (57 kDa) in their immunoblots. Several groups have since identified the 90–110 kDa band as the biologically relevant Nrf2 target, despite the predicted molecular weight of Nrf2 being 57 kDa [38], [39].…”
Section: Nrf2 Signaling In Response To Acute Exercisementioning
confidence: 99%